Voyages and beaches : Pacific encounters, 1769-1840 - Calder, Alex; Lamb, Jonathan, 1945-; Orr, Bridget (Book collections on Project MUSE., 1999)
What actually happened as Europeans and peoples of the Pacific discovered each other? How have their respective senses of the past influenced their understanding of the present? And what are the consequences of their meeting? In this collection of essays, scholars from European, Polynesian, and Settler backgrounds provide answers to these questions. Writing from, and between, a variety of disciplines (history, anthropology, Maori Studies, literary criticism, law, cultural studies, art history, Pacific Studies), they show how the Pacific reveals a more various and contradictory history than that supposed by such homogenizing metropolitan myths as the introduction of civilization to savage peoples, the general ruin of indigenous cultures by an imperial juggernaut, or the mimicry of European models by an abject population. They examine contact from both sides of beaches throughout Polynesia, exposing the many inconsistencies from which Pacific history is made. Some of the essays consider the extent to which traditional European ideas about organizing and legitimizing claims to territory and power were invoked and problematized in the South Pacific; some consider the violence endemic in such scenes; others examine the aesthetic discourses with which early travelers and settlers attempted to make sense of the Pacific in the aftermath of "discovery." But rather than reiterate the myths and anti-myths of conquest, these essays show how local differences have made and do make a difference. They emphasize the Pacific's capacity to absorb and transform the impact of Europe, an impact that has been as notable for its ambivalence and confusion as for its single-minded pursuit of hegemony. The editors develop these themes in a wide-ranging introduction that relates Pacific concerns to a more global set of theoretical and methodological problems, including current work in post-colonial and subaltern studies